The influence of micro-influencers and content marketing through customer engagement on purchasing decisions - Setiawan, Rudi; Salim, Muhartini (Universitas Wiralodra, 2024)
Technology has had a huge impact on the marketing field. In today's digital era, technology has completely changed the way we interact and communicate with customers. Instagram is the object of research because this platform has become one of the largest and most popular social media in the world. This research aims to determine the influence of micro-influencers and content marketing through customer engagement on product purchasing decisions on Instagram. The data obtained by this research is through a questionnaire from 100 respondents. Instagram users. This research data was processed using SEM (Structural Equation Modeling) using the SmartPLS4 application. The results of this research show the positive influence of Micro-influencers on Customer engagement, Content marketing on Customer engagement, Micro-influencers on purchasing decisions, Content marketing on purchasing decisions, Customer engagement on purchasing decisions, and Micro influencers on work decisions through customer engagement. Content marketing on employment decisions through customer engagement. Implementation for companies that market their products via Instagram is expected to use Micro-Influencers and Content Marketing to attract buyers and good customer engagement, resulting in purchasing decisions on the Instagram application.